2022
DOI: 10.3390/catal12111477
|View full text |Cite
|
Sign up to set email alerts
|

Methane-Assisted Iron Oxides Chemical Looping in a Solar Concentrator: A Real Case Study

Abstract: Recent interest in hydrogen as an alternative fuel for lowering carbon emissions is funding the exploration of new ways to cleanly produce this molecule. Iron oxides can be used within a process of chemical looping. More specifically, they can lose oxygens at extremely high temperature in an inert atmosphere. An alumina receiver could not stand the extreme thermal stress, while steel (AISI 316 and Inconel Hastelloy c-276) lasted enough for the reaction to start, even if at the end of the process the receiver m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…The system is composed of two motors to allow optimal orientation according to the time of day, and from the geographical coordinates of the site where the CSP is installed (Turin, 45.0676 • N, 7.6563 • E). Other useful geometric and technical parameters are listed in the following table (Table 1) and in previous studies [21,23]. The concentrator-receiver system is built using the Comsol Multiphysics 5.6 Inc. software (Burlington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system is composed of two motors to allow optimal orientation according to the time of day, and from the geographical coordinates of the site where the CSP is installed (Turin, 45.0676 • N, 7.6563 • E). Other useful geometric and technical parameters are listed in the following table (Table 1) and in previous studies [21,23]. The concentrator-receiver system is built using the Comsol Multiphysics 5.6 Inc. software (Burlington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This occurs most easily in the seasons from spring to autumn. The production of thermal energy is a surplus that is added to the production of electricity [19][20][21][22]. In this study, the CSP dish is integrated with a water storage tank, forming a system designed to provide hot water for integration into the Energy Centre's network.…”
Section: Introductionmentioning
confidence: 99%
“…The system is composed of two motors to allow optimal orientation according to the time of day, and from the geographical coordinates of the site where the CSP is installed (Turin, 45.0676 N, 7.6563 E). Other useful geometric and technical parameters are listed in the following table (Table 1), and in previous studies [18,20]. The concentrator-receiver system is built using Comsol multiphysics Inc. software (Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…This work primarily involves evaluating the performance of an existing CSP dish located at the Energy Center of Politecnico di Torino. One of the main objectives of this study is to also study thermal energy production with the CSP, after previous publications related to the electricity production [16][17][18][19]. The CSP dish is integrated with a water storage tank, forming a system designed to provide hot water for integration into the Energy Centre's network.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable improvements, also in terms of cyclability and repeatability must be achieved, not only for solar-driven thermochemical cycles but also for other applications. In the study of Borghero et al, a critical aspect was shown: the difficulty of working under real conditions by the receiver placed in the focal point of a CSP disc [22].…”
Section: Introductionmentioning
confidence: 99%